1995
DOI: 10.1128/jb.177.22.6552-6559.1995
|View full text |Cite
|
Sign up to set email alerts
|

Generation mechanism and purification of an inactive form convertible in vivo to the active form of quinoprotein alcohol dehydrogenase in Gluconobacter suboxydans

Abstract: Alcohol dehydrogenase (ADH) of acetic acid bacteria is a membrane-bound quinohemoprotein-cytochrome c complex involved in vinegar production. In Gluconobacter suboxydans grown under acidic growth conditions, it was found that ADH content in the membranes was largely increased but the activity was not much changed, suggesting that such a condition produces an inactive form of ADH (inactive ADH). A similar phenomenon could be also observed in Acetobacter aceti, another genus of acetic acid bacteria. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 28 publications
4
46
0
Order By: Relevance
“…It is interesting to see that inactive ADH is formed in G. suboxydans when the organism is grown under vigorous aeration in acidic pH. 10) It is said that a similar phenomenon also occurs in the genus Acetobacter. The highest concentration of acetic acid (about 5.5%) was detected after 10 days of incubation when the pH of the culture medium dropped from 3.5 to 2.9.…”
Section: Vinegar Fermentation Under Static Culturementioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to see that inactive ADH is formed in G. suboxydans when the organism is grown under vigorous aeration in acidic pH. 10) It is said that a similar phenomenon also occurs in the genus Acetobacter. The highest concentration of acetic acid (about 5.5%) was detected after 10 days of incubation when the pH of the culture medium dropped from 3.5 to 2.9.…”
Section: Vinegar Fermentation Under Static Culturementioning
confidence: 99%
“…9 ) Furthermore, an inactive ADH convertible in vivo to the active form is formed in Gluconobacter suboxydans and the generation mechanism and physiological function are under investigation. 10) Hot summer in these couple of years has brought indoor temperature increases beyond 30°C even in night time in many countries. That is a serious challenge to not only vinegar fermentation but also other fermentation industries, since they need a huge amount of cooling water to maintain the optimum fermentation temperature.…”
mentioning
confidence: 99%
“…pasteurianus SKU 1102, SKU 1106, and SKU 1111 (G. Theeragool et at., unpublished observations). Recently, Matsushita et al 30) reported the formation of inactive ADH when G. suboxydans was grown in acidic and high-aeration conditions. It is interesting to see that a similar phenomenon can be observed in A. aceti.…”
Section: Enzymesmentioning
confidence: 99%
“…The oxidoreductase activity of ALDH was measured spectrophotometrically in a Shimadzu UV-2401 PC UV-visible light (UVVis) spectrophotometer (Shimadzu, Kyoto, Japan) at pH 3.5 using potassium ferricyanide as an electron acceptor as described by Matsushita et al (22) or at pH 7.0 using PMS plus 2,6-dichlorophenolindophenol (DCPIP) as electron acceptors, as described previously (8). One unit of the enzyme activity is the amount of enzyme that catalyzes the oxidation of 1.0 mol of substrate per min under the indicated conditions.…”
mentioning
confidence: 99%